The effect of buoyancy force on structural damage: A case study. (October 2018) - Bikçe, Murat; Örnek, Murat; Cansız, Ömer Faruk
Abstract: In most decades, the height of structures and the number of basement floors have been increased especially in the valuable sites. By constructing the piles around the construction for safety purposes, a pool environment is occurred. Water accumulation in the excavation site due to various reasons might cause basement floors, forming a closed volume, to move upwards. This very risk is also prevalent for all the structural elements below soil in flood susceptible areas. This problem, which arises when necessary precautions are not taken, is generally overlooked by the engineer while aiming for the completed structure weight. Floating damage is completely different from the liquefaction of soil, which results from unexpected movements in a structure due to the loss of the bearing capacity of the soil. Unfortunately, this underestimated hazard is indicated in the standards and codes only for port structures in coastal areas. In this study, it is aimed to point out that the structural damage due to the buoyancy force can be avoided by paying attention to basic mechanical concepts and design procedures That's why, an office building in Hatay/Turkey which was damaged during construction as a result of the buoyancy force occurred in a flood has been chosen and examined as a case study.